PENYULUHAN PENCEGAHAN DAN PEMBERANTASAN PENYALAHGUNAAN, PEREDARAN GELAP NARKOBA (P4GN) DI DESA BINAAN TATAH LAYAP, KABUPATEN BANJAR - Aulia Rahim; Rakhmadhan Niah (Jurnal Bakti untuk Negeri, 2021)
There is more and more abuse of illegal drugs or better known as drugs. Drug abuse is increasing day by day. The daily increase in drug users is 0.065% of the total population of 200 million people or equal to 130,000 people per day. The purpose of this community service is to provide understanding, guidance, andstrengthen the role of community leaders in the context of eradicating drugs. The method used is through counseling to community leaders. The counseling was attended by 27 people from various elements of the Tatah Layap village community leaders. The conclusion of this event is that participants are enthusiastic about participating in counseling and will become pioneers in preventing, eradicating,abusing, and embezzling drugs in Tatah Layap Village.